The Relationship Between Anxiety and Numerical Literacy of Elementary School Students - Septiana Heni Hendrik; Rien Anitra; Buyung Buyung (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2024)
This study aims to: 1) Describe the level of mathematics anxiety of fifth grade students of SDN 6 Singkawang, 2) Describe the level of numeracy literacy of fifth grade students of SDN 6 Singkawang, 3) Describe the relationship between mathematics anxiety and numeracy literacy of fifth grade students of SDN 6 Singkawang. This type of research is quantitative research. The research design uses a correlation design. The population in this study were all fifth grade students of SDN 6 Singkawang. The sample used saturated sampling totaling 21 students. Data collection techniques used a mathematics anxiety questionnaire and a numeracy literacy test. Data analysis techniques used descriptive percentage tests and Pearson product moment correlation tests using Excel and SPSS 27. The results of the study showed: 1) students' mathematics anxiety was in the very low category with a percentage of 48%, 2) students' numeracy literacy was in the very low category with an average value of 49, 3) there was no significant relationship between students' mathematics anxiety and numeracy literacy. The correlation value is 0.118 and the correlation coefficient is in the very low category.